Analisis Pengaruh Kesiapan Teknologi dan Motivasi Kewirausahaan terhadap Dukungan Manajemen dan Keberhasilan Pemasaran Digital pada UMKM Pengrajin Alas Kaki di Jawa Timur - Saiful Arif, Mochamad; Zaki Fadhil, Achmad; Febrita Sarie, Rena (PRAGMATIS, 2025)
The purpose of the research is to analyze the influence of technology readiness and entrepreneurial motivation on the success of digital marketing through management support in MSMEs (Micro, Small, and Medium Enterprises) of footwear craftsmen in East Java. The research method uses a quantitative approach with a survey method. The population includes all MSME footwear craftsmen in East Java. A sample of 69 MSME footwear craftsmen in East Java was obtained through accidental sampling. Data were processed using SEM PLS 4. The results of the study show that Technology Readiness does not affect Management Support, Entrepreneurial Motivation affects Management Support, Management Support affects the success of Digital Marketing, Technology Readiness does not affect the success of Digital Marketing, Entrepreneurial Motivation affects the success of Digital Marketing, and Technology Readiness does not affect the success of Digital Marketing and Entrepreneurial motivation affects the success of digital marketing through management support in small and medium enterprises (SMEs) of shoe craftsmen in East Java. This finding is expected to provide strategic recommendations for shoe craftsman SMEs to enhance the effectiveness of their digital marketing.